2018
DOI: 10.5152/turkjsurg.2018.4126
|View full text |Cite
|
Sign up to set email alerts
|

Routine histopathological examination of gallbladder specimens after cholecystectomy: Is it time to change the current practice?

Abstract: A strategy of selective approach for histopathological examination of gallbladder specimens may be safe in areas with very low incidence of gallbladder carcinoma. Such selective strategy is more cost-effective, reduces the workload of pathologists, and does not appear to compromise patient outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 0 publications
1
10
0
Order By: Relevance
“…An additional 18 studies were identified during manual cross‐referencing, resulting in a total of 73 articles, including 232 155 patients, that were eligible for data analysis. These studies were then divided into those performed in countries with a low incidence (39) 6,18–55 and countries with a high incidence (34) 7,56–88 of GBC. Characteristics of all included studies are presented in Table S1 (supporting information).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…An additional 18 studies were identified during manual cross‐referencing, resulting in a total of 73 articles, including 232 155 patients, that were eligible for data analysis. These studies were then divided into those performed in countries with a low incidence (39) 6,18–55 and countries with a high incidence (34) 7,56–88 of GBC. Characteristics of all included studies are presented in Table S1 (supporting information).…”
Section: Resultsmentioning
confidence: 99%
“…5). Three studies 23,28,52 (5633 patients) from countries with a low incidence of GBC in which the surgeon systematically De Zoysa et al 20 Almuslamani et al 22 Genç et al 23 Ghimire et al 24 Byars and Pursnani 25 Cavallaro et al 26 Chin et al 27 Romero-González et al 28 Bawahab et al 29 De Werra et al 30 Ferrarese et al 31 Koshenkov et al 32 Ozgur et al 33 Panebianco et al 34 Elshaer et al 35 Ghnnam et al 36 van Vliet et al 6 Amiraslanov et al 37 Bali et al 38 Emmett et al 39 Lilic et al 40 Basak et al 41 Düzköylü et al 43 Patel et al 44 Al-Qahtani et al 45 Tatli et al 46 Uysal et al 47 Wrenn et al 48 Al Manasra et al 49 Benkhadoura et al 50 Charfi et al 51 Corten et al 52 Dincel et al 53 Geramizadeh et al 54 Olthof et al 55 456 of 129 059 Total Heterogeneity:…”
Section: Incidence Of Truly Incidental Gallbladder Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…All of the studies included in the review are in the English language and conducted in countries with a different incidence of GBC. These studies have been conducted in Asia and Europe except for one study in Mexico (Romero et al, 2012) and the other in Libya (Benkhadoura et al, 2019). These studies mainly focus The Newcastle Ottawa scale rates studies according to the selection, comparability and outcome assessment with a score range from 0 to 9.…”
Section: Study Characterizationmentioning
confidence: 99%
“…Incidental gallbladder carcinoma is found in 0.2%–2.9% of all cholecystectomies performed for gallstone disease 16. Adenocarcinoma accounts for almost 90% of GBC 12 14…”
Section: Discussionmentioning
confidence: 99%